DNA probes and nucleic acid amplification techniques to diagnose infectious diseases (Annals of Medical Research, 2021)
None
Keywords: s : Microbiology, diagnostic tests, PCR, LCR, TAS/3SR, SDA, QB replicase, bDNA, DNA probes